1999
DOI: 10.1046/j.1365-2141.1999.01791.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial depletion of tissue factor pathway inhibitor during subcutaneous administration of unfractionated heparin, but not with two low molecular weight heparins

Abstract: Summary. Tissue factor pathway inhibitor (TFPI) is released to circulating blood after intravenous (i.v.) and subcutaneous (s.c.) injections of heparins, and may thus contribute to the antithrombotic effect of heparins. We have recently shown that total TFPI activity, plasma free TFPI antigen, and heparin releasable TFPI were partially depleted during repeated and continuous i.v. infusion of unfractionated heparin (UFH), but not during s.c. treatment with a low molecular weight heparin (LMWH). The difference m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
5
25
0
Order By: Relevance
“…Since the differential effect of UFH and LMWH could also be explained by the different mode of administration in these studies, we performed a direct comparison of putative equivalent doses of UFH and two different LMWHs (dalteparin and enoxaparin) given by the subcutaneous route [48]. This study again found a significant depletion of TFPI associated with UFH but not with the two LMWHs.…”
Section: Differential Effect Of Ufh and Lmwhmentioning
confidence: 80%
See 1 more Smart Citation
“…Since the differential effect of UFH and LMWH could also be explained by the different mode of administration in these studies, we performed a direct comparison of putative equivalent doses of UFH and two different LMWHs (dalteparin and enoxaparin) given by the subcutaneous route [48]. This study again found a significant depletion of TFPI associated with UFH but not with the two LMWHs.…”
Section: Differential Effect Of Ufh and Lmwhmentioning
confidence: 80%
“…The release of TFPI results in a two-fold to fivefold increase in total TFPI activity [44,45], a three-fold to ten-fold increase in TFPI total antigen levels [33], and an eight-fold to fifteen-fold increase in TFPI free antigen levels [46,47]. After subcutaneous injection of either UFH or LMWH, the release is maximal after only 30-60 min as compared with the maximal anti-factor Xa and anti-factor IIa activities after 3-5 h [35, [47][48][49]. This rapid release of TFPI may involve rapid absorption of heparin fragments without anti-factor Xa and anti-factor IIa activities, but with retained ability to release TFPI.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, treatment with heparin by the subcutaneous route was also associated with depletion of TFPI but not with LMWHs [11]. The effects of C3 on plasma TFPI levels were investigated after repeated subcutaneous administration.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous administration of a LMWH (enoxaparin) resulted in larger increases in circulating TFPI levels than heparin [7]. In addition, plasma free TFPI antigen and heparin releasable TFPI were depleted during repeated or continuous treatment with heparin, but not during subcutaneous treatment with LMWHs [8,9,11]. In a recent study [10] with two different LMWHs, a clear dose-response relationship has been noted for dalteparin and enoxaparin on the release of endogenous TFPI.…”
Section: Introductionmentioning
confidence: 96%
“…LMWH confers the additional advantage of facilitating studies on extended therapy, since LMWH may be administered on an outpatient basis. Theoretical advantages include superior ability of LMWH (enoxaparin) to attenuate von Willebrand factor and increase TFPI [19].…”
Section: Rationale For Use In Acsmentioning
confidence: 99%